A novel bacterial strain Burkholderia sp. F25 capable of degrading diffusible signal factor signal shows strong biocontrol potential - Yu, Hongxiao; Chen, Wen-Juan; Bhatt, Kalpana; Zhou, Zhe; Zhu, Xixian; Liu, Siqi; He, Jiehua; Zhang, Lian-Hui; Chen, Shaohua; Wang, Huishan; Liao, Lisheng (Frontiers in Plant Science, 2022)
Vast quantities of synthetic pesticides have been widely applied in various fields to kill plant pathogens, resulting in increased pathogen resistance and decreased effectiveness of such chemicals. In addition, the increased presence of pesticide residues affects living organisms and the environment largely on a global scale. To mitigate the impact of crop diseases more sustainably on plant health and productivity, there is a need for more safe and more eco-friendly strategies as compared to chemical prevention. Quorum sensing (QS) is an intercellular communication mechanism in a bacterial population, through which bacteria adjust their population density and behavior upon sensing the levels of signaling molecules in the environment. As an alternative, quorum quenching (QQ) is a promising new strategy for disease control, which interferes with QS by blocking intercellular communication between pathogenic bacteria to suppress the expression of disease-causing genes. Black rot caused by Xanthomonas campestris pv. campestris (Xcc) is associated with the diffusible signal factor (DSF). As detailed in this study, a new QQ strain F25, identified as Burkholderia sp., displayed a superior ability to completely degrade 2 mM of DSF within 72 h. The main intermediate product in the biodegradation of DSF was identified as n-decanoic acid, based on gas chromatography-mass spectrometry (GC-MS). A metabolic pathway for DSF by strain F25 is proposed, based on the chemical structure of DSF and its intermediates, demonstrating the possible degradation of DSF via oxidation-reduction. The application of strain F25 and its crude enzyme as biocontrol agents significantly attenuated black rot caused by Xcc, and inhibited tissue maceration in the host plant Raphanus sativus L., without affecting the host plant. This suggests that agents produced from strain F25 and its crude enzyme have promising applications in controlling infectious diseases caused by DSF-dependent bacterial pathogens. These findings are expected to provide a new therapeutic strategy for controlling QS-mediated plant diseases.